Peran Koperasi Bagi Anggota Dan Harapan Anggota Terhadap Koperasi - Azhar Solihin, Shofwan (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2023)
Cooperatives exist as wheels of the economy that are able to fill every line of the economy, from micro to macro. As we know, Cooperative is a joint effort of a group of people who have the same interests with the aim of improving the welfare of its members. Cooperatives are business entities whose activities are managed by their own members, in Indonesia cooperative business entities are under the auspices of the Ministry of Cooperatives and Micro, Small and Medium Enterprises. Cooperatives as one of the people's economic institutions need to be developed and strengthened in order to foster economic democracy as one of the foundations for creating a prosperous and just society. Members hope that the cooperative can realize the desire regarding the establishment of a business unit for the procurement of raw materials, with this new business unit members can develop members' businesses even better by meeting all existing needs, in that way cooperatives can indirectly promote to the surrounding community or members bakers who have not yet joined the cooperative and can join in order to benefit from the cooperative.